Assessment of macrofungi diversity in Perlis State Park, Perlis, Malaysia - Ag. Ahmadni, Ag. Shaffie; Shamsul Kamar, Nura Adilla; Amir Hadi, Muhamad; Terhem, Razak (Department of Environmental Sciences, Arak University, 2024)
Macrofungi play a diverse role in ecosystems, serving as decomposers, sources of food, and providers of medicinal benefits to humans for millennia. However, the status of macrofungi diversity in Perlis State Park is poorly understood. This study aims to identify the diversity of macrofungi species in Perlis State Park. Sampling was conducted using both opportunistic and selective approaches along a transect line comprising 10 trails during the rainy season between 2019 and 2023. Identification was based on the morphological characteristics of macrofungi. A total of 69 species of macrofungi were discovered, including 59 species from Basidiomycota and 10 species from Ascomycota. These species can be categorized into eight groups, namely Cup (2), Gill (20), Shelf and Bracket (16), Bolete (7), Coral (6), Jelly (6), Earthball and Puffball (4), and Tooth (4) fungi. Of the identified macrofungi species, 33 are confirmed to be edible. Additionally, three species from the Cordycipitaceae and Ophiocordycipitaceae families within the suborders of Ascomycota are entomopathogenic. Some microfungi fall under the category of 'Least Concern (LC)' according to the IUCN Red List. Our study highlights the importance of macrofungi diversity in Perlis State Park, which can be instrumental for conservation and educational purposes.